La competitividad de la industria vitivinícola a través del enoturismo en México en el estado de Querétaro y España en la región de Galicia - Maravilla Calderón, Lesly Laura (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
This research aims to determine how it has influenced productivity, wine tourism, and wine quality in the wine competition in the state of Queretaro in Mexico and Spain in the region of Galicia with a qualitative and quantitative approacha, with a transactional or cross-sectional design and exploratory scopes, descriptive and correlational in which is considered that productivity, wine tourism and wine quality are the determining factors in the wine competitiveness of Mexico and Spain , which have placed the wine industry in the international market. The research has theoretical ideas like the developments that have taken foreign trade as well as a theoretical context of competitiveness in order to determine the factors leading to the wine industry is competitive in the national and international markets. To set that productivity, wine tourism and wine quality determine the competitiveness of the wine industry in Mexico and Spain it made a questionnaire with five values and mixed type, based on the Likert scale, to make mixed it made this questionnaire to four wine tourism events, two wineries in the state of Queretaro in Mexico and two wineries in Spain in the region of Galicia which will subsequently be emptied information in the SPSS program to analyze the results and so achieve corroborate the assumptions made in this investigation. As for the results of the field work is concluded that it approved the assumptions made in this investigation which claim that productivity, wine tourism and wine quality are variables that determine the competitiveness of the wine industry the state of Queretaro in Mexico and Spain in the region of Galicia.

La presente investigación tiene como objetivo conocer cómo ha influido la productividad, el enoturismo, y la calidad del vino en la competitividad vitivinícola en el estado de Querétaro en México y en España en la región de Galicia con un enfoque cualitativo y cuantitativo, con un diseño transaccional o transversal y alcances tanto exploratorios como descriptivo y correlacional en el cual, se considera que la productividad, el enoturismo y la calidad del vino son variables determinantes en la competitividad vitivinícola de México y España, los cuales han colocado a la industria vitivinícola dentro del mercado internacional. La investigación tiene como bases teóricas la evolución que ha tenido el comercio exterior así como un contexto teórico de la competitividad para así determinar las variables que conllevan a que la industria vitivinícola sea competitiva en el mercado nacional e internacional a través del enoturismo. Para establecer que la productividad, el enoturismo y la calidad del vino determinan la competitividad de la industria vitivinícola en México y España se aplica un cuestionario con cinco valores de tipo mixto, tomando como base la escala tipo Likert para hacerlo mixto a los asistentes a cuatro eventos enoturísticos, dos bodegas vitivinícolas en el estado de Querétaro en México y dos bodegas vitivinícolas en España en la región de Galicia el cual posteriormente será vaciada la información en el programa SPSS para poder analizar los resultados y así lograr corroborar las hipótesis planteadas en esta investigación. En cuanto a los resultados del trabajo de campo se llega a la conclusión de que se aprueban las hipótesis planteadas en esta investigación las cuales afirman que la productividad, el enoturismo y la calidad del vino si son variables que determinan la competitividad de las industria vitivinícola en el estado de Querétaro en México y en España en la región de Galicia.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2016-0449; Productividad; Enoturísmo; Calidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1020